Sejarah Gerakan Politik Pemuda di Jakarta Sekitar Proklamasi - Utomo, Satriono Priyo (Estoria: Journal of Social Science and Humanities, 2021)
The history of the Indonesian youth political movement in 1928 not only inherited national politics with the ties of "imagine of Indonesia" as a homeland, nation and language, namely Indonesia. But it also gave birth to the view that youth is the core of change. This view became the belief of Indonesian youth in the 1940s to be involved in the revolutionary wave of "imagine of Indonesia" in a more critical and progressive manner in political actions. This paper aims to explain youth activism in Jakarta around a more advanced proclamation, accelerating from national politics to populist politics. There were two strongest youth node organizations in Jakarta at that time, Asrama Menteng Raya 31 and Prapatan 10. Both of them brought together young people from different ethnic and national backgrounds. But the youth political movement in the 1940s had a more populist political tone with its political activities carrying out political education work in order to mobilize people's awareness of the struggle for independence. Then the youth in Jakarta formed an organizational node called the Angkatan Pemuda Indonesia (API), which contributed to the historical events of the grand meeting at Ikada Square on September 19, 1945. Where Sukarno spoke as President of Indonesia for the first time in front of a mass mobilized by youth after the reading of the proclamation on August 17, 1945.